Mental Illness Stigma: Limitations of Crisis Intervention Team Training - Haigh, Cassidy Blair (Criminal justice policy review, 2020)
As police departments in the United States strive to improve their capacity to effectively engage individuals with mental illness (IMI), Crisis Intervention Team (CIT) training has become increasingly common. Limited empirical work has studied the effectiveness of CIT, and available studies demonstrate split evidence on the effectiveness of the approach. Variation in previous findings may indicate that CIT inadequately addresses key factors that create challenges for officers when engaging IMI, such as mental illness stigma. Survey data collected from 185 officers were analyzed to assess whether mental illness stigma affects officers’ perceptions of preparedness for engaging IMI beyond CIT training itself. Findings suggest that although there are few differences in perceptions of preparedness between officers who have completed CIT training and those who have not completed CIT training, variation in levels of mental illness stigma explain differences in officers’ perceptions of preparedness to engage IMI. Policy recommendations are discussed.